Upgrading of railway station Bukit Mertajam for Keretapi Tanah Melayu Berhad at Jalan Stesen, 14000 Bukit Mertajam, Seberang Perai Tengah, Pulau Pinang / Noorsharini Isha’ak - Isha’ak, Noorsharini (Faculty of Architecture, Planning and Surveying, 2011)
This project is about to upgrade a railway station at Bukit Mertajam for Keretapi Tanah Melayu Berhad at Jalan Stesen, 14000,Bukit Mertajam,Seberang Prai Tengah, Pulau Pinang.The client of this project is Keretapi Tanah Melayu Berhad.This project proposed upgrading works which includes the interior space in the railway station from the entrance, lobby, counter ticket, waiting area, cafe, kiosk and the office. The objective of this project to solve the problem of space available at the train station, design and produce a new space to meet the comfort, produce a systematic flow for staff and customer, upgrade the station to become more perfect and has its own image. In conclusion, the new design for railway station at Bukit Mertajam will have the characteristic and client’s need besides the suitable concept to be shown and should benefited to the user and client’s.